Effect of drench to stem base and foliage spray with Trichoderma harzianum on powdery mildew disease (Leveillula taurica) in macrotunnel-grown tomato plants - OSCAR ALEJANDRO MARTÃNEZ-JAIME, CARLOS MANUEL BUCIO-VILLALOBOS* and (Indian Phytopathology, 2016)
The objective of this work was to study the efficiency of C4 and CM35 experimental strains of Trichoderma harzianum for controlling Leveillula taurica in tomato plants under macrotunnel conditions. T. harzianum was applied to individual tomato plants of the cultivar Gabriela in three forms: foliar spray, drenching and a combination of both. A control without T. harzianum was also included. The results showed low significant differences in the health of foliage among the different treatments where T. harzianum was applied; nevertheless spraying the foliage and the combination of this with drench to stem base of the C4 strain showed better results. The control was always in the statistical group with the highest levels damage the disease. We recommend the possibility of using T. harzianum to improve the health of tomato plants, but it is necessary to reaffirm the results with other experiments.